1799 N.J. Laws 609; 1800 N.J. Laws 441 - (:unkn) unknown (My University, 1799)
Eliminated non-whites from the militia. Persons who were granted militia exemptions (e.g., physicians, clergy) had to pay a three-dollar annual fee. In case the militia were "called into actual service," exempted persons too would be liable to serve.
Keywords: MILITIAS